The vitamin A nutrition of prepartum Hereford heifers fed dry land rations with or without supplements of alfalfa or fish liver oil - Selleck, Dean B., author; Washburn, L. E., advisor; Wheeler, S. S. (Sherman Shaw), 1901-, committee member; Bourne, Richard F., committee member; Patton, A. R. (Alva Rae), 1908-, committee member; Barney, C. W., committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Keywords: Cattle; Feeds; Nutrition